PEMANFAATAN LIMBAH CAIR TAHU SEBAGAI PUPUK ORGANIK CAIR DAN PEMBERIAN PUPUK ANORGANIK NPK TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) DENGAN MENGGUNAKAN SISTEM HIDROPONIK WICK - Karina Marcella Br Sebayang, Emma; M. Idris; Nila Selvia, Irda (Universitas Cokroaminoto Palopo, 2025)
Liquid tofu waste is one type of organic fertilizer as a waste product from the tofu industry that functions as a supplier of nutrients such as nitrogen, phosphorus and potassium, and also easily releases these nutrients for use by plants. NPK fertilizer has a fairly high nitrogen, phosphorus and potassium content so that it can contribute macro nutrients that are very much needed. This research method uses a Randomized Block Design (RAK) with 6 treatments consisting of 3 treatments of liquid tofu waste poc and 3 treatments of inorganic NPK fertilizer and 3 repetitions. The first treatment on liquid tofu waste poc is (P0) 0% which consists of 5000 ml of distilled water or, the second treatment is P1 45% (POC 2,250 ml + 2,750 ml of distilled water) and the third treatment is P2 55% (POC 2,750 ml + 2,250 ml of distilled water). The first NPK treatment was (N0) 0 g NPK fertilizer, the second treatment was N1 (1 g NPK fertilizer) and the second treatment was N2 (1.5 g NPK fertilizer). The results showed that the combination of liquid tofu waste POC and NPK fertilizer gave significant results in increasing the growth of mustard greens (Brassica juncea L.). The conclusion obtained from this study was the best treatment P2N2 (POC 45% + NPK 1.5 g).